Sural Artery Bypass in Buerger’s Disease: Report of a Case - Matsumoto, Harunobu (The Editorial Committee of Annals of Vascular Diseases, 2012)
A 72 year-old man was admitted to the hospital to receive treatment for resting pain and an ulcer, which had developed on an amputation stump, 4 months after he had undergone a thrombectomy, below-the-knee popliteal-dorsal pedis artery bypass of his left leg, and digital amputation of his 2nd toe. Angiography demonstrated diffuse arterial and bypass occlusion in his left leg that did not include a sural artery, which was the main collateral. Therefore, the patient underwent reversed saphenous vein bypass from the common femoral artery to the medial sural artery. His leg pain disappeared, and the ulcer healed promptly.